Chromothripsis 18 in multiple myeloma patient with rapid extramedullary relapse - Smetana, Jan; Oppelt, Jan; Štork, Martin; Pour, Luděk; Kuglík, Petr (Molecular cytogenetics, 2018)
Background: Catastrophic chromosomal event known as chromothripsis was proven to be a significant hallmark of poor prognosis in several cancer diseases. While this phenomenon is very rare in among multiple myeloma (MM) patients, its presence in karyotype is associated with very poor prognosis. Case presentation: In our case, we report a 62 year female patient with rapid progression of multiple myeloma (MM) into extramedullary disease and short overall survival (OS = 23 months). I-FISH investigation revealed presence of gain 1q21 and hyperdiploidy (+ 5,+ 9,+ 15) in 82% and 86%, respectively, whileIgHrearrangements, del(17)(p13) and del(13)(q14) were evaluated as negative.Whole-genome profiling using array-CGH showed complex genomic changes including hyperdiploidy (+ 3,+ 5,+ 9,+ 11, + 15,+ 19), monosomy X, structural gains (1q21-1q23.1, 1q32-1q44, 16p13.13-16p11.2) and losses (1q23.1-1q32.1; 8p23.3-8p11.21) of genetic material and chromothripsis in chromosome 18 with 6 breakpoint areas. Next-generation sequencing showed a total of 338 variants with 1.8% (6/338) of pathological mutations inNRAS(c.181C > A; p.Gln61Lys) or variants of unknown significance inTP53, CUX1andPOU4F1. Conclusions: Our findings suggest that presence of chromothripsis should be considered as another important genetic hallmark of poor prognosis in MM patients and utilization of genome-wide screening techniques such as array-CGH and NGS improves the clinical diagnostics of the disease.